Increasing Quantitative and Qualitative Yield of Calendula officinalis L. by Using Bio-Fertilizer - M Hoseini Mazinani; A Hadipour (Institue of Medicinal Plants, ACECR, 2014)
Background: Because the excessive use of chemical fertilizers had harmful effects, bio-fertilizers using are suitable alternative for supply of safe food, healthy environment and human health. Objective: To evaluate the effect of bio-fertilizers on the quantity and quality yield of calendula medicinal plant. Methods: This study conducted in the research farm of Islamic Azad University (Shahr-e-Ray Branch) based on a randomized complete blocks design with three replications. Treatments were Nitroxin, Super nitro plus, Mycorrhizae, animal manure, chemical fertilizer (NPK) and control (no fertilizer). Results: The bio-fertilizers using had a significant effect on the most of studied quantity and quality parameters. Effect of bio-fertilizers was significant (p≤0.05) on dry matter of flower and fresh yield and (p≤0.01) on fresh weight of flower and essential oil yield of calendula. Biofertilizer had a significant effect on main constituents, Muurolol (epi-alpha) and alpha-Cadinol (%) (p≤0.01). Conclusion: Biofertilizers had a positive and significant effect on yield of essential oil and also maximum yield of essential oil was observed by Nitroxin treatment.